Magmatic and metamorphic evolution of the Latimojong Metamorphic Complex, Indonesia. (15th April 2022) - Hakim, A.Y.A.; Melcher, F.; Prochaska, W.; Meisel, T.C.
Graphical abstract: Highlights: New mineralogical and geochemical data of rocks comprising the Latimojong Metamorphic Complex (LMC), are presented. Magmatic minerals were partly preserved during metamorphism, provide hints to the magmatic & tectonic evolution of the LMC. Protoliths of the metamorphic rocks are identified as ash fall material, basalts and andesites. A shift of isotopic composition in carbonates is the result of the interaction of hydrothermal fluids with host rocks. Metamorphic conditions are in the high pressure (up to 12 kb) – low temperature (up to 415 °C) range. Abstract: In the Latimojong Metamorphic Complex of Sulawesi, Indonesia, magmatic minerals are occasionally preserved in metabasites and have been overprinted by a metamorphic assemblage of chlorite-actinolite-pumpellyite. The relict of magmatic minerals preserved within metamorphic rocks are used as a potential discriminant for magma chemistry and tectonic processes. The analysis of the stable isotopes of carbon and oxygen as well as Raman spectroscopy in carbonates are used to reconstruct the origin of carbon. Within the same metabasite sample heterogeneous chromian spinel comprising (i) high-Al chromite (#Cr = 100xCr/(Cr + Al) = 40–60); (ii) high- Cr chromite (#Cr > 70) implies spinel formation from a single batch magma but at different stages of fractional crystallization. Growing clinopyroxene phenocrysts in island-arc basalt (IAB)-type melt trapped floating chromian spinel crystals that developed through time to progressively more-Al depleted compositions. Whole-rock data provide evidence of a collision between the Indo-Australian and Eurasian Plates. The rare earth element (REE) patterns of metasedimentary rocks exhibit enrichment of large ion lithophile elements, light REE, and high REE relative to the primitive mantle and might be interpreted as slab dehydration during high-pressure metamorphism at mantle depths. Metamorphic conditions documented in the mineral compositions and structures (graphite) point to high pressure (up to 12 kb) and low temperature (300–415 °C) metamorphism typically observed in subduction zones. Mineral and whole rock geochemistry indicates that the Latimojong Metamorphic Complex underwent a tectonic evolution and accretion history similar to other metamorphic complexes in the southern parts of Sulawesi (i.e. Barru and Bantimala), although protoliths and metamorphic P-T conditions may have varied.